2019
DOI: 10.1590/1678-992x-2018-0056
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of superfine grinding method on antioxidant and antifungal characteristic of Brazilian green propolis extract

Abstract: Green propolis is found only in Brazil and due to its important biological characteristics, the food industry views it as a rich source of bioactive compounds. However, an extract must be produced for its application, which is difficult considering the rigid characteristics of raw propolis. Superfine grinding, a process capable of reducing particle size, enables the extraction of most bioactive compounds in propolis. This study evaluated the influence of grinding on size characteristics, antioxidant and antifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
(42 reference statements)
0
8
0
1
Order By: Relevance
“…In tea, the reduction in particle size led to a higher decrease in almost all phenolic compound catechins measured 24 . In addition, in some cases, the granulometric characteristics do not influence the amount of bioactive compounds extracted 25 . For example, the total phenolic content and antioxidant activity of green propolis were increased regardless of the particle size.…”
Section: Resultsmentioning
confidence: 99%
“…In tea, the reduction in particle size led to a higher decrease in almost all phenolic compound catechins measured 24 . In addition, in some cases, the granulometric characteristics do not influence the amount of bioactive compounds extracted 25 . For example, the total phenolic content and antioxidant activity of green propolis were increased regardless of the particle size.…”
Section: Resultsmentioning
confidence: 99%
“…Augusto‐Obara et al. (2019) indicated that the TEAC values of Tunsanian propolis ranged from 109.76 to 252.9 μmol TEAC/g. Gargouri et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some cases, the granulometric characteristics do not influence the degree of bioactive extraction caused by grinding. For example, superfine grinding of green propolis enhanced the extraction of bioactive compounds, resulting in increased total phenolic content and antioxidant activity, regardless of the particle size [ 117 ].…”
Section: Food-processing Techniques and Their Effects On Polyphenols Content And Bioavailabilitymentioning
confidence: 99%
“…Further grinding decreased the antioxidant activity (DPPH assay). [ 115 ] Superfine grinding method Brazilian green propolis TPC TPC increased (regardless of the particle size) Antioxidant activity increased (measured by ABTS and DPPH, regardless of the particle size) [ 117 ] Abbreviations: TPC—total phenolic content, TAC—total anthocyanin content, TPA—total phenolic acid content; TFC—total flavonoid content, HSTS—high-temperature short-time; PEF—pulsed electric field; sig—significant, n.s.—non significant; DPPH—2,2-diphenyl-1-picrylhydrazyl; ABTS—2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid; FRAP—ferric reducing antioxidant power; CUPRAC—cupric-reducing antioxidant capacity; GAE—gallic acid equivalent; RSA—radical scavenging activity. …”
Section: Table A1mentioning
confidence: 99%